Clonal Propagation of Date Palm through Somatic Embryogenesis - Rao, A. M.; Reddy, S. K.; Rao, V. R. M.; Bhalla, J. K. (Indian Forester, 2001)
Shoot tip explants from three cultivars of Date palm viz. Sukari, Barhee and Kalas were used for callus initiation. They were cultured in MS medium supplemented with 40 mg/l NAA or NOA and 1.5 gm/l charcoal. Cultures were subcultured every week for three months and incubated in dark conditions. The callus was transferred to low auxin media for induction of somatic embryogenesis. The somatic embryos were developed into plantlets in hormone-free medium. The plants were acclimatized in the glass house and finally transferred to the field.